PERANCANGAN DAN IMPLEMENTASI APLIKASI UJIAN SEKOLAH BERBASIS KOMPUTER ATAU COMPUTER BASED TEST (CBT) DI SMK NEGERI 1 KABUPATEN SORONG - Marcell Petrus Saptono; Herry Widjasena (Electro Luceat, 2019)
Conventional Test System means that the test is done using paper and pencil or the current term Paper-Based Test (PBT), the constraints and shortcomings of the PBT system are no longer effective & efficient. Sorong State Vocational School 1 still uses Paper-Based Test (PBT) to carry out School Exams. Conventional systems must be replaced by computer information technology using Computer-based Tes This research resulted in an offline Computer Based Test (CBT) based test system at SMK Negeri 1 Kabupaten Sorong. The CBT system makes it easier for student and teacher examinations, the use of exam paper is reduced, examination of exam results is more efficient and effective, it can save time and money. This application system can be used for grading assignments, daily tests and midterm, final exam can even be used as a national exam tryout. The exam analysis system can make it easier for teachers or principals to accept student exam results and analyze students' abilities more quickly. Students at SMK Negeri 1 Sorong Regency will become accustomed to examinations using a computerized system or using an android mobile phone.